GeneralY268007 GeneralY268007
  • 03-11-2022
  • Mathematics
contestada

Use f(x)=-x-8 and g(x) = x² + 8x − 15 to answer the following: a) f(1) + g(–3) b) g(−9) − f(–7)

Respuesta :

HarleiC532842 HarleiC532842
  • 03-11-2022

ANSWER:

a) -37

b) 9

Given:

f(x)=-x-8 and g(x) = x² + 8x − 15

a) f(1) + g(–3)

f(1) = 1 - 8 = -7

g(-3) = -3² + 8(-3) - 15 = 9 - 24 - 15 = -30

f(1) + g(–3) = -7 + (-30)

= -7 - 30

-37

b) g(−9) − f(–7):

g(-9) = -9² + 8(-9) - 15 = 81 - 72 - 15 = -6

f(-7) = -7 - 8 = -15

Thus,

g(−9) − f(–7) = -6 - (-15)

= -6 + 15

= 9

​

Answer Link

Otras preguntas

Approximately how much shaking does a magnitude 7 earthquake produce compared to a magnitude 5 earthquake?
2 cups of flour makes of a loaf of bread. How much flour is needed for 1 whole loaf?
if the store purchased a kitchen appliance for $42 and sold it for $58.80, what was the percent markup?
PLEAASE HELP!!! estimate 11 4/5 divided by 3 1/5
Work out the value of (-/-5)2 X (-/-3)2
Does the justice system neglect forgiveness commonlit answer key.
pls answer this it's due today​
what is the acid name for H(HS) need help asap
what were muslims in north africa and spain called
Instructions for Questions 1-3: Each of the sentences below may contain a grammar or usage error. Read each sentence and then identify its error, if there is on